On the algebra of elliptic curves - Tomasz Brzezinski (Proceedings of the Edinburgh Mathematical Society, 2023)
It is argued that a nonsingular elliptic curve admits a natural or fundamental abelian heap structure uniquely determined by the curve itself. It is shown that the set of complex analytic or rational functions from a nonsingular elliptic curve to itself is a truss arising from endomorphisms of this heap.